A KARAKTERISTIK DAN PENGETAHUAN MAHASISWI KEBIDANAN TERHADAP KESIAPAN MENIKAH - Nina Primasari (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
The high number of young couples who divorce due to unpreparedness in undergoing marriage indicates that many young couples have not actually paid attention to marriage readiness. Lack of readiness to marry both partners is one of the most dominant causes causing divorce. Student age is a time of adjustment to new life patterns and new social expectations as adults. Related to this, students need to have self-readiness in various challenges and difficulties, as well as in adjusting independently and being responsible for their new roles, including roles in facing self-readiness to enter the world of work, marriage and family life, as well as roles as members of society. This study aims to determine the characteristics and knowledge of midwifery students on marriage readiness. Designa research is analytical research with a cross sectional approach. The population is all midwifery students, the number of samples obtained is 74 people with random sampling techniques. The results of the study were obtained P value of 0.017, so this means that there is a relationship between the knowledge of female students and readiness for marriage. Thus, premarital education classes and counseling on marriage preparation can be held so that female students who will face marriage are better prepared and responsible for starting a family for the creation of a quality next generation of the nation and the decline in divorce rates in Indonesia.